Seni Sebagai Media Dakwah - Muhammad Yusuf (Ath Thariq Jurnal Dakwah dan Komunikasi, 2018)
Art is a thing that contains beauty, fun and everything that is fascinating and exciting. This is because basically the art itself is created to give birth to fun and give birth to the beauty and pleasure is the desire and the human penchant because it is the nature of human naluriyah endowed Allah SUBHANAHU WA TA’ALA . Throughout the history of human life has never been found a people who distanced themselves from bebagai kinds of art. Da'wah means is, calling, inviting, inviting, calling, encouraging Muslims to do good. Islamic da'wah is a call of obligation that is not determined by social structure, position or color difference of skin but for all people who claim to be Muslim. The duty of da'wah should also be tailored to the abilities and skills of each person (subject), meaning that everyone does not have to perform da'wah activities just like a speaker, but based on their ability and expertise. An artist can preach through his artwork even a doctor can preach by treating patient. Dakwah media in the time of Rasullulah Shulallahu’alaihi wa Sallam and companions is very limited, which revolves around da'wah qauliyyah bi al-lisan and da'wah fi'liyyah bi al-uswah, coupled with the media use of very limited letters. A century later dakwah using media. That is, storytellers and articles are introduced. In this context, da'wah by using new media such as newspapers, magazines, short stories, films, radio, television, painting, advertisement, performances because of the performance of singing, music and other art media can encourage and help the da'wah performers in carrying out their duties.